Comparison of the Methods for Diagnosing the Carpal Tunnel Syndrome - Dobilinskas, Aurimas; Knystautas, Saulius; Braziulis, Kęstutis; Rutkauskas, Irmantas; Pilipaitytė, Loreta (Lietuvos chirurgija, 2023)
Background. Carpal tunnel syndrome is the most common and widespread peripheral neuropathy in the world. The diagnostic testing methods for the carpal tunnel syndrome are based on anamnesis data, objective and instrumental inspection. Electroneuromyography is the main instrumental test when carpal tunnel syndrome is suspected. An ultrasound imaging may also be performed. Objective. To determine the effectiveness, sensitivity and specificity of instrumental diagnostics methods used to diagnose the carpal tunnel syndrome, and to compare them. Methods. Diagnostic testing – ultrasound and electroneuromyography was applied to persons under study. The area of the median nerve (mm2) was assessed during the ultrasound examination. The results of the electroneuromyography study evaluated the response speed of the sensory impulse (ms), the speed of the motor impulse response (ms). Later, the tests, their sensitivity and specificity were evaluated and compared. Results. 30 patients participated in the study, of which 26 (86.7%) were women, 4 (13.3%) were men. Electroneuromyography was found to be both sensitive and specific for a measure of sensory propagation velocity, 76.2 and 75%, respectively (p = 0.042); of motor propagation speed – 100 and 75% (p = 0.040). Ultrasonography is sensitive (87.5%) but nonspecific (66.7%) (p = 0.008). The study showed that the ultrasound dimension strongly, directly and reliably correlates with the sensory impulse response rate (p < 0.001), and the ultrasound dimension moderately, directly and reliably correlates with the motor impulse response rate (p < 0.001). Conclusions. Carpal tunnel syndrome can be suspected by ultrasound measurement of the area of the median nerve, but the test is only sensitive but non-specific. Electroneuromyography can confirm the diagnosis of carpal tunnel syndrome, as the test is both sensitive and specific. Comparing the studies, a strong, direct and reliable relationship between the results of the ultrasound and the electroneuromyography testing was established.